2015
DOI: 10.1590/s0102-6720201500s100020
|View full text |Cite
|
Sign up to set email alerts
|

Baros Method Critical Analysis (Bariatric Analysis and Reporting System)

Abstract: Introduction: Although it has received several criticisms, which is considered to be the most effective method used for global assessment of morbid obesity surgical treatment, still needs to be updated. Objective: Critical analysis of BAROS constitution and method. Method : BAROS as headings was searched in literature review using data from the main bariatric surgery journals until 2009. Results: Where found and assessed 121 papers containing criticisms on BAROS constitution and methodology. It has some failur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 19 publications
0
8
1
5
Order By: Relevance
“…These mean scores were used to compare quality of life between patients who underwent surgery and control group who were scheduled for surgery. Changes in this score after LSG was reported in some studies (8,(13)(14)(15) but in our study this comparison did not revealed statistically difference (P = 0.275).…”
Section: Discussioncontrasting
confidence: 67%
See 2 more Smart Citations
“…These mean scores were used to compare quality of life between patients who underwent surgery and control group who were scheduled for surgery. Changes in this score after LSG was reported in some studies (8,(13)(14)(15) but in our study this comparison did not revealed statistically difference (P = 0.275).…”
Section: Discussioncontrasting
confidence: 67%
“…Oria et al began developing a system to assess and report outcomes after bariatric surgeries that included analysis Copyright © 2018, Journal of Minimally Invasive Surgical Sciences. This is an open-access article distributed under the terms of the Creative Commons Attribution-NonCommercial 4.0 International License (http://creativecommons.org/licenses/by-nc/4.0/) which permits copy and redistribute the material just in noncommercial usages, provided the original work is properly cited of changes in QOL according to weight loss and improvements in obesity-related comorbidities (7,8). It was specifically created to be included in to the bariatric analysis and reporting outcome system (BAROS).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This technique has the advantage of not generating problems of malabsorption because it does not change the contact of the food with the intestinal walls and with their respective digestive enzymes. Moreover, because it does not have digestive anastomosis, it offers a lower risk of postoperative complications compared to other techniques 3 , 6 , 7 , 15 , 20 , 26 .…”
Section: Introductionmentioning
confidence: 99%
“…No entanto, inúmeras críticas têm sido elencadas por pesquisadores, devido a limitações no seu desenho, como a impossibilidade de comparar o estado de saúde do pré com o pós-operatório, valores expressos em categorias nominais para cada domínio agrupando o mesmo modo indivíduos com características e resultados diferentes, limitação das comorbidades listadas para serem avaliadas, entre outros. 28 Os resultados alcançados reforçam a importância da perda de peso para redução dos fatores de risco, melhora de doenças associadas, melhora na qualidade de vida e na mortalidade. Uma das limitações do estudo foi o desenho transversal, ao utilizar uma única análise para caracterização de um aspecto, o que dificulta a realização de associações e comparações.…”
Section: Variávelunclassified